2020
DOI: 10.7202/1070525ar
|View full text |Cite
|
Sign up to set email alerts
|

Voter à l’échelle municipale au Québec : significations et portée chez certains jeunes électeurs

Abstract: Au Québec, les élections municipales se caractérisent par la faible mobilisation qu’elles suscitent. Cette réalité est encore plus frappante chez les jeunes électeurs. Si les causes de cette abstention demeurent encore largement méconnues, la spécificité de l’échelle municipale est souvent mise de l’avant. Ce constat invite à délaisser les analyses plus traditionnelles du vote pour considérer l’acte électoral comme un geste symbolique d’identification à un territoire, porteur d’un ensemble de valeurs, suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Some participants explained that they have a better knowledge of the municipal world and are better equipped to look for the right information to vote. This is not unrelated to the results of the study by (Breux and et Vallette, 2020), which showed that young Montreal voters, aged 18 to 35, look to their parents for information about municipal elections. The authors explain that young voters have not yet learned about the municipal political system, making it impossible for them to acquire information on their own.…”
Section: Discussionmentioning
confidence: 66%
“…Some participants explained that they have a better knowledge of the municipal world and are better equipped to look for the right information to vote. This is not unrelated to the results of the study by (Breux and et Vallette, 2020), which showed that young Montreal voters, aged 18 to 35, look to their parents for information about municipal elections. The authors explain that young voters have not yet learned about the municipal political system, making it impossible for them to acquire information on their own.…”
Section: Discussionmentioning
confidence: 66%